Analysis of the impact of the digital economy system on carbon emissions and carbon footprint from the perspective of high-quality development - Li, Youhui; Chen, Beichuan; Guo, Lifeng; Kang, Jie (Frontiers in Environmental Science, 2025)
The application of digital technology and the emergence of new economic forms have accelerated economic and social dynamic circulation, and the digital economy industry has achieved positive results in enhancing regional carbon emission efficiency. Therefore, exploring the carbon footprint of the digital economy system and the new development model of “dual circulation” from the perspective of high-quality development is important to ensure its healthy development. This study is based on the theory of high-quality development. It uses panel models, spatial econometric models, and other methods for empirical analysis of the level of digital economy development and carbon emission efficiency in more than 25 provinces in China and also of their impact effects. The results indicated that under the post-epidemic situation, the digital economy level of various provinces in China has improved to varying degrees, especially in the Beijing, Tianjin, Hebei, and Pearl River Delta regions, where the improvement effect is significant. The carbon emission efficiency showed a decreasing trend from east to west in the spatial dimension. The digital economy was significantly positively correlated with carbon emission efficiency at the 1% level. In comparison, the negative effects of urbanization level and government macro intervention variables were significant at the 5% and 10% levels. The adjustment of industrial structure, energy technology, and development of the digital economy had significant spatial spillover effects and heterogeneity. When the digital economy improved carbon emission efficiency, a certain degree of peripheral inhibition was observed. From the perspective of high-quality development, the digital economy needs to focus on the “simultaneous realization and maintenance” of economic and ecological benefits and actively adjust the industrial structure and energy optimization based on regional differences.